Perbandingan Model Pembelajaran Instruksi Langsung dan Model Pembelajaran Kooperatif terhadap Hasil Belajar Senam Lantai - M. Taufiqurrahman. M; Mikkey Anggara Suganda; Adiman Adiman (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. The results of this experimental study can increase students motivation to learn physical education. The learning outcomes of students before and after being given treatment by applying the direct instruction learning model and the cooperative learning model to the learning outcomes of floor exercises. Materials and methods. The research method used in this study was experimental. Regarding the improvement in learning outcomes before and after applying the direct instruction learning model and the cooperative learning model to floor gymnastics learning outcomes, it can be seen that in the pre-test, which was conducted before applying the direct instruction learning model and the cooperative learning model to floor gymnastics learning outcomes, the average student learning score was 59 out of a maximum score of 71. Results. From the categorisation results, it can be shown that there were 1 student or 2.8% in the very low category, 29 students or 80.6% in the low category, 6 students or 16.7% in the medium category, and no students in the high and very high categories. Based on the categorisation results, it can be stated that the students' learning outcomes were low. This can be seen in the percentage value, which was highest in the low category because the class average score was only 64.81 out of a total of 36 students. Conclusion. Therefore, it can be concluded that the learning outcomes for floor exercises are homogeneous. Thus, the research hypothesis was tested using parametric statistics, namely the two-sample t-test and the paired t-test. These results also show that students who participated in direct instruction and cooperative learning models achieved good learning outcomes for floor exercises.